Impact of Blockchain Technology on Supply Chain Management Efficiency and Transparency in Pakistan - Huzaifa, Imran (International Journal of Supply Chain Management, 2024)
Abstract Purpose: The aim of the study was to influence the impact of blockchain technology on supply chain management efficiency and transparency Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: A study on the impact of blockchain technology on supply chain management in Pakistan revealed significant improvements in efficiency and transparency. Through blockchain integration, supply chain processes experienced reduced delays and increased automation, leading to streamlined operations. Transparency was notably enhanced, with real-time tracking of goods and secure data sharing among stakeholders, mitigating risks of fraud and error. These findings suggest that adopting blockchain technology holds promise for enhancing supply chain management in Pakistan by fostering greater efficiency and transparency. Unique Contribution to Theory, Practice and Policy: Diffusion of innovations theory, information processing theory & resource dependency theory may be used to anchor future studies on the impact of block chain technology on supply chain management efficiency and transparency. Encourage supply chain stakeholders to adopt blockchain solutions for enhanced transparency, traceability, and efficiency. Advocate for regulatory frameworks that promote the adoption of blockchain technology in supply chains while addressing concerns related to data privacy, interoperability, and standardization.